Explaining the Best Management Practices for Maintaining European Honey Bee Colonies - Michael K. O'Malley; James D. Ellis; Jerry W. Hayes (EDIS, 2010)
ENY158, a 4-page fact sheet by M. K. O’Malley, J.D. Ellis and G. W. Hayes, Jr., outlines and explains the 12 recommendations listed in the voluntary agreement between Florida beekeepers and state officials to minimize the spread of African honey bees. Published by the UF Department of Entomology and Nematology, October 2010.